Stretcher force and seat movement - Kleshnev, V. (BioRow, 2019)
There have been numerous BioRow clients who have asked the same question: "Does the BioRow system measure stretcher force?" The answer is yes, we can do it with a number of methods (RBN 2013/08, 2017/05), but the installation of stretcher force sensors is a very time-consuming and non-trivial task, because boats of various brands have a large variety of stretcher designs. Therefore, we do not measure the stretcher force directly in the BioRow standard testing routine (where installation time is very limited, from 20min for 1x to 70min for 8+), but can estimate it based on the seat movement. Here, relationships between the stretcher force and seat movements will be analysed.